2015
DOI: 10.1007/s12663-014-0704-y
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Ameloblastoma in the Free Fibula Flap: Review of Literature and an Unusual Case Report

Abstract: Ameloblastoma is the second most common odontogenic tumor of the oral cavity with the primary site being the mandible. The ratio of maxillomandibular involvement however is 5:1 in favor of the mandible. The most common complaint is a painless swelling over the mandibular area. Despite its benign nature, ameloblastoma has a high local recurrence rate, with the most recurrences seen within 5 years after operation. Biopsy and radiological evaluation may be helpful in differentiating the subtypes of ameloblastoma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
6
0
2
Order By: Relevance
“…Laborde et al and Becelli et al reported no recurrence in his study of 7 patients' postsegmental resection [ 41 , 8 ]. Similar reports are documented by Vayvada et al, Chaine et al, and Basat et al on postresection and free flap reconstruction [ 13 , 15 , 34 , 42 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Laborde et al and Becelli et al reported no recurrence in his study of 7 patients' postsegmental resection [ 41 , 8 ]. Similar reports are documented by Vayvada et al, Chaine et al, and Basat et al on postresection and free flap reconstruction [ 13 , 15 , 34 , 42 ].…”
Section: Discussionsupporting
confidence: 88%
“…Invasion of the periosteum can lead to spread of the tumour cells to the soft tissue. Inadequate resection of the hard and soft tissues beyond a tumour would cause recurrence [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was related to inflammation, trauma and nutritional deficiencies. Yet, recent data strongly indicate that unique genetic abnormalities cause the development of ameloblastoma [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Ameloblastoma usually presents as a painless slowly growing tumour which can become a large and expansile swelling causing tooth loosening and displacement as well as facial asymmetry. CT scan is considered the gold standard for diagnosis [1,4,6]. Recurrence of ameloblastoma after surgical resection is not an uncommon event which reaches up to 15% even after adequate surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…"solid/multicystic" was dropped because it has no biologic signi cance, but its clinical and radiographic features sometimes was unique [1]. Records in literatures [5][6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (table 1)among 25 patients which are about 10 patients graft bone CT showed multicystic [6-8, 12, 15, 18, 19, 21, 22]. Only 12 patients showed the pathological ndings, 6 showed acanthomatous ameloblastoma [5-8, 12, 17, 18, 21, 22].…”
Section: Discussionmentioning
confidence: 99%